The Development of Gametophyte Sterilization Method for Liverworts Acrolejeunea fertilis (Reinw., Blume and Nees) Schiffn. In vitro Culture - Mouleidi Dwi Putri; Windri Handayani; Astari Dwiranti; Andi Salamah; Niarsi Merry Hemelda; Afiatry Putrika (HAYATI Journal of Biosciences, 2021)
In vitro culture gametophytes of leafy liverworts often have problems in their sterilization process. These problems due to the high level of contamination and the fragile structure of the gametophyte leafy liverworts. The structures can be easily to damage after exposure to disinfectant. This study aimed to observe the concentration and the exposure time of “Bayclin” commercial bleach to suppress contamination with the viability of Acrolejeunea fertilisgametophytic explants. This research was conducted using control and 6 combination treatments with “Bayclin” concentration (1.00%, 1.25%, and 1.50%) and exposure time 60 and 120 seconds, then accompanied by the addition of Tetracycline 2.5 mg/ml. The qualitative parameters observed were the explant color, the type and location of contamination, and the growth of explants. The quantitative parameters were the percentage of contamination, the percentage of growth, and the number of new branches. The results showed that “Bayclin” 1.25% and 1.50% with 60 seconds exposure time has the lowest percentage of contamination which is 70% until the 7th days after planting. The most common type of internal contamination from the explant is bacteria and fungi. However, the growth of the new branch still occurs in some explants even though it has been contaminated and browned.